(untitled) (Research, Society and Development, 2022)
The present study aims to study the correlation of fruit and vegetable consumption with levels of daily physical activity. Using secondary data obtained from the National School Health Survey in its third edition (2015), with children and adolescents aged 13 to 17 years (162,608 evaluated) through a questionnaire. To identify the association between fruit and vegetable consumption and weekly amount of physical activity, linear regression models were used, in three stages: Individual characteristics: sex, age group; Socioeconomy: region of the country, mother’s education; Food consumption: fruit consumption, vegetable consumption. All statistical analyzes were performed using SPSS® 22, with a statistical significance level of p≤0.05. A higher level of physical activity is observed among those who have "regular" fruit, girls 229,32; boys 335.13, vegetables girls 222.07; boys 320.78 or consumption of vegetables and fruits girls 248.34; boys 350.28. A negative association was observed between “irregular consumption of fruits” p<0.001, “irregular consumption of vegetables” p<0.001 and weekly amount of physical activity p<0.001.